(untitled) (ELang | An English Language Education Journal, 2017)
The research paper entitled “Series of Picture as a Means of Improving Students’ Writing Recount Text Ability” is submitted to the English Educational Sciences of Bale Bandung University as a partial fulfillment of the requirenment for taking Sarjana Pendidikan Degree. The focus of the research is that media series of picture could improve students’ desire in learning writing. The students could be more excited and easier to understand the text. Pre – experimental design was used in this research. The second grade students of SMP 1 Solokanjeruk which consist 32 students were chosen as the population. They were asked to fill out the first performance test (Pre-Test) then got the treatment (Series of Picture) and finally the students were asked to fill out the second performance test (Post-Test). Furthermore the score of post-test was higher than pre-test. The result of pre–test and post–test score were analyzed through the dependent t-test formula, with df = N – 1 = 32-1 = 31 at the level of significance 0.05 for two tailed was 2.021. As the derived t was bigger than that of the t-table 2.64 > 2.021, the null hypothesis (Ho) was rejected, and alternative of hypothesis (Ha) was accepted, stating that there was significant different in students’ score before and after treatment using series of picture as a means of improving writing recount text ability. In other words, this method was effective to improve students’ ability in writing recount text. From the questionnaire, most of the second grades of junior high school in Solokanjeruk gave positive responses toward series of picture as a means of improving writing recount text ability. They felt happy in learning English especially when they were learning writing recount text, they did not get the difficulties moreover, learning recount text using series of picture was easier to understand and very helpful in improving student’s writing skill.